2006
DOI: 10.1002/pmic.200500902
|View full text |Cite
|
Sign up to set email alerts
|

Proteome modifications of the medicinal leech nervous system under bacterial challenge

Abstract: Once considered as lacking intrinsic immune mechanisms, the CNS of vertebrates is now known to be capable of mounting its own innate immune response. Interestingly, while invertebrates have been very useful in the interpretation of general vertebrate innate immunity mechanisms, only scarce data are available on the immune response of nervous tissue within this group. This study provides new data on the innate immune response of medicinal leech Hirudo medicinalis CNS. We identified several spots in 2-D gels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…These results are consistent with the data obtained by the bottom-up approach, supporting the tentative conclusion that gliarin and antimicrobial-neurotrophic factors are implicated in the adult nerve cord regeneration. In addition, our observations complement those obtained by genomic and 2D-Gel proteomic studies [3], [5], [7], [9] ( Table 3 ). By comparison, Blackshaw and collaborators have reported, in studies using subtractive cDNAs library from regenerating and non-regenerating central ganglia, the presence of leech homologues of mammalian genes with established functions, including the cytoskeletal proteins actin, tubulin and Protein 4.1, ATP synthase, the neuron-specific protein synapsin, Cysteine Rich Intestinal Protein (CRIP), myohemerythrin and a novel protein ReN3, exclusively expressed in invertebrates [3], [4], [21], [22].…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…These results are consistent with the data obtained by the bottom-up approach, supporting the tentative conclusion that gliarin and antimicrobial-neurotrophic factors are implicated in the adult nerve cord regeneration. In addition, our observations complement those obtained by genomic and 2D-Gel proteomic studies [3], [5], [7], [9] ( Table 3 ). By comparison, Blackshaw and collaborators have reported, in studies using subtractive cDNAs library from regenerating and non-regenerating central ganglia, the presence of leech homologues of mammalian genes with established functions, including the cytoskeletal proteins actin, tubulin and Protein 4.1, ATP synthase, the neuron-specific protein synapsin, Cysteine Rich Intestinal Protein (CRIP), myohemerythrin and a novel protein ReN3, exclusively expressed in invertebrates [3], [4], [21], [22].…”
Section: Resultssupporting
confidence: 88%
“…Similarly on-going proteomic studies of the leech CNS performed by our group have shown that some molecules detected by transcriptomic approaches, e.g. cytoskeletal and metabolic proteins, foldases, calcium sensors, kinases and neurohemerythrin (reflecting specific cytoskeletal rearrangements linked to cell migration), vesicular trafficking as well as the modulation of synaptic activity, are also observed in excised adult ganglia challenged by bacterial toxins [7], [9].…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations